THE USE OF ANIMATED MEDIA ON SHOOTING LEARNING OUTCOMES IN BASKETBALL GAMES IN CHILDREN AGED 10-11 YEARS - Yopi Meirijal; Sumbara Hambali; Sony Hasmarita; Yovhandra Ockta (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study investigates the effectiveness of animated media in improving basketball shooting performance among children aged 10–11 years through an experimental method, revealing that animation-based instruction significantly enhances training outcomes compared to conventional methods. The research was conducted at Cimahi Mandiri 2 Elementary School with a total of 40 students participating in extracurricular basketball activities. Using a total sampling technique, participants were randomly divided into two equal groups: one received animated media during training, and the other followed traditional instruction without animation. A basketball shooting test was used to assess performance improvements. The results demonstrated that the group exposed to animated media showed a significant increase in shooting performance (t=23.59>t-table=2.262), while the non-animation group also improved but to a lesser extent (t=12.68>t-table=2.262). Furthermore, a comparative test between the two groups yielded a significant difference (t=25.98>t-table=2.101), indicating a stronger impact of animated media. In conclusion, animated media significantly improves basketball shooting skills in children, and the results and conclusions are consistent with the study’s objectives.